Heterogeneous route for transfer hydrogenation reactions of ketones using Ru(II)Cymene complex over modified benzene-organosilica (PMOB) - Lazar, Anish; Silpa, S.; Prabhakaran, Vinod C.; Singh, A. P. (Molecular Catalysis, 2017)
An inorganic-organic hybrid catalyst, Ru(II)Cym@PMOB, was synthesized by anchoring of [Ru(II)Cl-2(Pcymene)](2) complex which is derived from a reaction between hydrated ruthenium(III) trichloride and ocphellandrene over aminofunctionalized benzene-organosilica (PMOB). In the context of secondary alcohol synthesis from ketones, transfer hydrogenation (TH) reactions are convenient compared to conventional hydrogenation reactions owing to its lower activation energy and ambient pressure and mild temperature reaction" conditions. The synthesized catalysts were characterized by CHN analysis, XRD, ICP, N-2-sorption analysis, TG & DTA, FFIR,C-13 & 29Si solid NMR, UV-vis, TEM, SEM and XPS. The catalytic activities of neat [Ru(II)C-12(p-cymene)]2 complex and Ru(II)Cym@PMOB were evaluated in transfer hydrogenation (TH) of ketones (-97%) and compared with conventional hydrogenation reactions (-5%) where molecular H-2 was used. The results showed Ru(II)Cym@PMOB as highly active catalyst towards transfer hydrogenation (TH) reaction of acetophenones compared to neat [Ru(II)Cl-2(p-cymene)(12) complex. The heterogeneity of Ru(II)Cym@PMOB was confirmed by Sheldon's test. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Conventional Hydrogenation Reactions; Ru(II)Cym@PMOB; Transfer Hydrogenation Reaction; [Ru(II)Cl2(p-cymene)]2 complex

Highly selective aqueous phase hydrogenation of phenols over nanostructured RuO2 on MCM-41 catalysts - Betsy, K. J.; Lazar, Anish; Vinod, C. P. (Nano-Structures & Nano-Objects, 2018)
Selective aqueous phase hydrogenation of phenol as well as its derivatives is important for the synthesis of chemical intermediates which are crucial for the manufacture of high-tonnage commodities and a multitude of value added platform chemicals. Herein, we report a facile catalyst made of highly dispersed small RuO2 nanoparticles supported on mesoporous MCM-41 using one-pot approach. The optimal 5RuO2-MCM-41 catalyst with particle size 6-8 nm showed excellent activity and selectivity in aqueous phase hydrogenation of phenol and other functionalized substrates, which are building blocks of lignin, to corresponding cyclohexanol products without any additives. These catalysts showed better stability and can be reused several times without any significant drop in activity which proves the heterogeneity of the immobilized oxide catalyst.